Behold, your house is left to you : the theological and narrative place of jerusalem temple in Luke's gospel - Rice, Peter H. (Peter Harrison) (Eugene, Oregon : Pickwick Publications, 2016)
This book explores the place of Jerusalem and its Temple in Luke's Gospel, paying attention both to the Third Gospel's narrative and theological dynamics and to the historical and rhetorical milieu in which Luke composed his narrative. It argues for a portrait of the Jerusalem Temple in Luke's Gospel that is complex, multifold, and coherent, one comprised of interwoven strands constituting an engaging and intertextual response to the pressing theological concerns of the Evangelist's day.
Machine generated contents note: pt. 1 Introduction -- 1. Reading Luke: Narrative, Subtlety, and Echoes of Scripture -- 2. Theodicy in the Ancient and Lukan Worlds -- pt. 2 Jerusalem Temple in Luke's Gospel -- A Reassessment -- 3. Jerusalem Temple in Luke 1 -- 2 -- 4. Jerusalem Temple in Luke 3 -- 19 -- 5. Jerusalem Temple in Luke 19 -- 24 -- 6. Conclusion.
Includes bibliographical references and index.
Online resource, title from PDF title page (EBSCO, viewed December 22, 2016).
Master record variable field(s) change: 050
Keywords: Temple of Jerusalem (Jerusalem) -- In the Bible; Bible. -- Criticism, interpretation, etc; Temple of Jerusalem (Jerusalem); Bible; RELIGION -- Judaism -- General; Temple of Jerusalem (Jerusalem) in the Bible; Electronic books; Criticism, interpretation, etc